Integrated Reactor-Separator for Mercury Determination by Using FIA-CV-AAS Technique - Wahyuningjati, Mukti
Abstract : The ability of mercury compounds as depigmentation material has already know thus many of cosmetic companies using mercury as whitening cream ingredient. Mercury determination in whitening cream by modifying reactor-separator into a single integrated system which have both of the function has been done. This method based on flow injection analysis and cold vapor atomic absorption spectrophotometry technique (FIA-CV-AAS). Parameters which influence the result of measurements has been studied. The developed method has given a good analytical performance. It is proofed with precision value for this method, state as coefficient variant 7.29% (10 g.L-1) and 3.59% (50 mg.L-1) and detection limit value are 3.50 g.L-1. The linear dynamic range can be gained from concentration 1 g.L-1 up to 100 g.L-1 with correlation coefficient 0.9968. Accuracy of this method showed by percentage of recovery is more than 95% and the signal increment for 50 g.L-1 and 100 g.L-1are 2.12 and 3.38 respectively. This method has been applied for determination of trace level concentration of mercury in whitening cream.